How diverse is tree planting in the Central Plateau of Burkina Faso? Comparing small-scale restoration with other planting initiatives - Valette, M.; Vinceti, B.; Traoré, D.; Traoré, A.T.; Yago-Ouattara, Emma Lucie; Kaguembèga-Müller, F. (MDPI, 2019)
In the Sahelian region, different approaches are being used to halt environmental degradation and restore tree cover, with varying degrees of success. Initiatives vary according to projects’ objectives, type of land to restore, and technical practices used (natural regeneration, farmer-managed assisted regeneration, enrichment planting, etc.). This study investigates tree planting choices and selection of tree seed sources in some villages of the Central region of Burkina Faso. The study targeted 96 farmers and compared planting practices adopted by farmers involved in small-scale forest restoration using fences, with those not involved in this initiative. The objective was to understand what portfolio of tree species were planted, what factors influenced tree species selection, what tree seed sources were used, what collection practices were generally adopted, and whether there were significant differences between types of farmers. The results showed that the use of fencing to promote forest restoration support the planting of a more diverse portfolio of tree species than other small scale efforts and includes a greater representation of indigenous trees. Fenced plots have therefore a conservation value in landscapes where the diversity of tree species is progressively declining. In addition to the use of fences, some other key factors affect tree planting, mainly land tenure, availability of diverse tree seed sources, and availability of land. Farmers tend to collect directly most of the planting material they need, but in the majority of cases they do not follow recommended best practices. In light of the ambitious forest restoration targets of Burkina Faso and the need to provide diverse options to rural communities to enhance their resilience vis-à-vis increasing environmental challenges, strengthening the capacity of farmers in tree planting and establishing a robust tree seed systems are crucial targets